ANALISIS MANAJEMEN SARANA DAN PRASARANA DALAM MENDUKUNG KEGIATAN PEMBELAJARAN DI SMAIT QONITA ISLAMIC BOARDING SCHOOL - Nawafil, Hafidzah; Karimah, Dhiva Rivatul; Damayanti, Delis; Rizah, Rosita (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to conduct an in-depth analysis of facility and infrastructure management and its contribution to supporting learning activities at SMAIT Qonita Islamic Boarding School. This study examines how the planning, procurement, and maintenance of facilities are integrated to simultaneously meet academic and boarding needs. This study applies a mixed method with a triangulation design. Qualitative data was obtained through field observations and in-depth interviews with school management to understand the managerial process. Quantitative data was collected through questionnaires distributed to teachers and students to measure the level of satisfaction and effectiveness of facility use. The data was analyzed by combining the results of qualitative data reduction and descriptive statistics from the questionnaire. The results showed that the management of facilities and infrastructure at the school had met the minimum educational service standards with excellence in the integration of boarding school-based facilities. Analysis of the questionnaire data shows that the level of satisfaction of teachers and students is in the “Very Good” category, especially in terms of the availability of digital learning media. However, obstacles were found in the synchronization of routine maintenance of boarding school facilities, which required more intensive coordination between the school unit and the boarding house.